Pola Asuh Orang Tua dalam Menanamkan Nilai-Nilai Kristiani Remaja Usia 13-18 Tahun (International Forum of Researchers and Lecturers, 2025)
Instilling Christian values ​​in adolescents in Indonesia is a strategic effort to form strong character, ethics, and spiritual awareness. In addition to having an impact on individuals, this also creates harmony in a pluralistic society. The family is the first place to build a foundation of faith through teaching, praying together, and being a role model. Parenting patterns greatly influence the growth of adolescent faith. Therefore, Christian families are expected to not only provide material needs, but also attention and love that comes from God to foster adolescent spiritual values. This study aims to determine the form of parenting patterns in instilling Christian values ​​in adolescents aged 13–18 years, as well as the obstacles faced. The method used is qualitative with a naturalistic approach, involving 13 informants. Data were collected through observation, interviews, and documentation. The results of the study showed three parenting patterns, namely democratic, authoritarian, and permissive, with the authoritarian pattern being the most dominant. The obstacles faced by parents include educational factors, a less conducive environment, economy, and parental busyness.